2018
DOI: 10.1111/jnc.14340
|View full text |Cite
|
Sign up to set email alerts
|

What autoantibodies tell us about the pathogenesis of Parkinson's disease

Abstract: image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some studies have detected autoantibodies to α-synuclein (36,37) and autoreactive T cells that recognize specific α-synuclein epitopes in patients with PD (38), thus indicating that immune reactions participate in the pathophysiology of PD. In addition, studies have revealed that B cells contribute to the pathogenesis of PD (39), including deposits of immunoglobulin G (IgG) found on dopaminergic neurons (40), Lewy bodies coated with IgG (41), and increased levels of anti-α-synuclein antibodies in the cerebrospinal fluid and the blood (36,37). Aberrant functioning of the immune system, as aforementioned, has been proposed as a critical component of susceptibility to and progression of PD (14).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have detected autoantibodies to α-synuclein (36,37) and autoreactive T cells that recognize specific α-synuclein epitopes in patients with PD (38), thus indicating that immune reactions participate in the pathophysiology of PD. In addition, studies have revealed that B cells contribute to the pathogenesis of PD (39), including deposits of immunoglobulin G (IgG) found on dopaminergic neurons (40), Lewy bodies coated with IgG (41), and increased levels of anti-α-synuclein antibodies in the cerebrospinal fluid and the blood (36,37). Aberrant functioning of the immune system, as aforementioned, has been proposed as a critical component of susceptibility to and progression of PD (14).…”
Section: Discussionmentioning
confidence: 99%